Academic accommodation of students with special needs in open/ distance education (2010)
The presence of individuals with special needs in any society is one reality that cannot be denied anymore, This study therefore, investigated academic accommodation of students with special needs in the open/distance learning mode, The study is a descriptive survey in 5 purposively selected tertiary institutions running open/distance learning programmes and 93 academic heads of departments were sampled. Data obtained from the survey through a structured questionnaire were analysed by frequency counts, simple percentages, means and standard deviations, Results revealed that there were 170 academic accommodation services in all the institutions sampled and the preparation of lecturers was low in academic accommodation of students with special needs. It was therefore, recommended that institutions operating open/distance 'mode of learn should get there programmes and physical environments modified to cater for students with special needs because they are an integral part of their potential student population.